Epidemiology and economic burden of measles, mumps, pertussis, and varicella in Germany: a systematic review - Damm, Oliver (Int J Public Health, 2016)
OBJECTIVES: Despite the availability of vaccines and the existence of public vaccination recommendations, outbreaks of vaccine-preventable childhood diseases still cause public health debate. The objective of this systematic review was to provide an overview of the current epidemiology and economic burden of measles, mumps, pertussis, and varicella in Germany. METHODS: We systematically reviewed studies published since 2000. The literature search was conducted using PubMed and EMBASE. Also, we used German notification data to give an up-to-date overview of the epidemiology of the four diseases under consideration. RESULTS: Thirty-six studies were included in our review. Results suggest that there is still considerable morbidity due to childhood diseases in Germany. Studies providing cost estimates are scarce. Comparative analyses of different data sources (notification data vs. claims data) revealed a potential underestimation of incidence estimates when using notification data. Furthermore, several studies showed regional differences in incidence of some of the diseases under consideration. CONCLUSIONS: Our findings underline the need for improved vaccination and communication strategies targeting all susceptible age and risk groups on a national and local level. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00038-016-0842-8) contains supplementary material, which is available to authorized users.